Deep Brain Stimulation in the Media: Over-Optimistic Portrayals Call for a New Strategy Involving Journalists and Scientists in Ethical Debates - Gilbert, Frédéric; Ovadia, Daniela (Frontiers in Integrative Neuroscience, 2011)
Deep brain stimulation (DBS) is optimistically portrayed in contemporary media. This already happened with psychosurgery during the first half of the 20th century. The tendency of popular media to hype the benefits of DBS therapies, without equally highlighting risks, fosters public expectations also due to the lack of ethical analysis in the scientific literature. Media are not expected (and often not prepared) to raise the ethical issues which remain unaddressed by the scientific community. To obtain a more objective portrayal of DBS in the media, a deeper collaboration between the science community and journalists, and particularly specialized ones, must be promoted. Access to databases and articles, directly or through science media centers, has also been proven effective in increasing the quality of reporting. This article has three main objectives. Firstly, to explore the past media coverage of leucotomy, and to examine its widespread acceptance and the neglect of ethical issues in its depiction. Secondly, to describe how current enthusiastic coverage of DBS causes excessive optimism and neglect of ethical issues in patients. Thirdly, to discuss communication models and strategies to enhance media and science responsibility.